2021
DOI: 10.3390/en14185907
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Cost Impacts of Food Waste in University Canteen from a Life Cycle Perspective

Abstract: Food waste has caused double waste of resources in the food itself and the food supply chain of production, transportation, cooking, and processing, resulting in unnecessary greenhouse gas emissions and economic losses. This paper first conducted the quantification of students’ food waste and the collection of canteens operation data in the three canteens at Taiyuan University of Technology (China) in 2019 through the weighing method and interview. Then an integration of Life Cycle Assessment and Life Cycle Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In three canteens of a Chinese university, considering environmental and cost impacts, Li et al ( 2021 ) found that the total amount of FW with 22,000 students was 246.75 t/year, the carbon footprint caused by FW was 539.28 t CO2-eq, and the cost was €647,348.94. The staple food (cooked wheat-based foods and rice products) is the highest (46.14%) contributor to the FW in this sample, whereas the remainder consists of vegetables and soy products (28.34%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In three canteens of a Chinese university, considering environmental and cost impacts, Li et al ( 2021 ) found that the total amount of FW with 22,000 students was 246.75 t/year, the carbon footprint caused by FW was 539.28 t CO2-eq, and the cost was €647,348.94. The staple food (cooked wheat-based foods and rice products) is the highest (46.14%) contributor to the FW in this sample, whereas the remainder consists of vegetables and soy products (28.34%).…”
Section: Resultsmentioning
confidence: 99%
“…Reducing FW is also a social responsibility of universities and an avenue for creating a positive public image when several people, including some of their students, are food-insecure (Kaur et al, 2021 ). FW is central to global sustainability efforts, making universities that enhance their environmental stewardship through initiatives to reduce FW and conducting research about reducing it, attractive to students interested in sustainability and environmental programs (Li et al, 2021 ). Therefore, involving students in the sustainability education process through applied and cooperative approaches to resolve the FW problem can become transformative for their education, independently from any future career path these may take.…”
Section: Introductionmentioning
confidence: 99%
“…119,120 Consumers were also especially targeted as an important aspect to mitigate environmental impacts of FLW. Raising awareness on the importance of reducing FLW and benefiting environmental sustainability, 22,46,79,104,121,122 and education on saving food (especially in schools) via courses and knowledgebased competition 53,108,110 or the use of well-calibrated equipment (especially for farmers 123 ), were mostly deemed as important ways in combating FLW and reducing environmental impacts. On the other hand, dietary structure change (e.g., substituting or reducing beef consumption 124,125 and increasing the consumption of plant food 110,126 ) has also been found as a promising way to achieve environmental stress reductions.…”
Section: Characteristics Of the Environmental Impacts Of Flw 331 Embo...mentioning
confidence: 99%
“…Another significant issue in reaching carbon neutrality is the management of food waste and food supply chains of production, transportation, cooking, and processing, which result in unnecessary greenhouse gases. This issue was addressed from a life cycle perspective in [19]. The authors quantified students' food waste and collected canteen operation data in the three canteens at Taiyuan University of Technology (China) in 2019 through the weighing method and interviews.…”
Section: Overview Of the Papers In This Special Issuementioning
confidence: 99%